EFFECT OF NEW HERBAL PREPARATIONS ON SOME INDICATORS OF APOPTOSIS IN RATS WITH ACUTE TOXIC HEPATITIS - Navruzovna, Kurbanova Nodira; Khidoyatovna, Inoyatova Feruza; Sultonovna, Omonova Gavkhar; Kadirovna, Rakhimova Zumrad (International Journal of Psychosocial Rehabilitation, 2020)
Purpose of the research: a comparative study of the anti-apoptotic effect of catacin, geranyl, cavergal compared to carlsil in a model of acute toxic liver damage with heliotrin. Material and methods. To achieve this goal, studies were conducted on 118 male adult rats. The model of acute toxic damage (ATD) was reproduced by a single subcutaneous injection of heliotrin at a dose of 200 mg/kg of animal body weight in 110 rats, 8 rats made up the intact group. On the 3rd day of the introduction of the toxicant, the surviving animals were divided into 5 groups: 1) ATD + physiological saline at a dose of 0.5 ml/100 g body weight (control) of 20 rats; 2) ATD + carsil (comparison group) 19 rats; 3) ATD + catacin 19 rats; 4) ATD + geranyl of 19 rats; 5) ATD + cover 18 rats. The drugs were administered intragastrically daily in the morning at 100 mg / kg for 6 and 12 days. 24 hours after the final administration of herbal preparations, the animals were killed, the content of cytochrome C and TNF-α was determined in the blood by the enzyme immunoassay. For statistical processing of the results, Excel and OriginPro7.5 software packages (OriginLab Corporation, USA) were used. Results. Determining the level of cytochrome C and TNF-α in the blood of rats with ATD their increase in 34-43 and 7.7-11.1 times. Pharmacotherapy of ATD with carlsilum for 6 and 12 days led to a decrease in the high values of these parameters by 2-2.85 and 1.61-1.98 times, by catacin - 2.75-4.16 and 2.86-3.83 times, geranyl - 3.35-4.44 and 3.28-3.95 times, cavernal - 3-4.32 and 1.58-1.93 times relative to the values of the untreated group of rats. It should be noted that in all groups the level of cytochrome C remained high. Conclusion: experimental pharmacotherapy of ATD with herbal preparations significantly slowed down the processes of apoptosis, this was more pronounced when using catacin, geranyl and cavergal.